Silence Speaks Volumes: The Effectiveness of Reticence in Comparison to Apology and Denial for Repairing Integrity- and Competence-Based Trust Violations - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2007)
Prior research on responses to trust violations has focused primarily on the effects of apology and denial. The authors extended this research by studying another type of verbal response that is often used to respond to trust violations but has not been considered in the trust literature: reticence. An accused party may use reticence in a sincere and even legitimate attempt to persuade a trustor to withhold judgment. Yet, by considering information diagnosticity and belief formation mechanisms through which verbal responses influence trust, the authors argue that reticence is a suboptimal response because it combines the least effective elements of apology and denial. Specifically, reticence is a suboptimal response to an integrity violation because, like apology, it fails to address guilt. And reticence is a suboptimal response to a competence violation because, like denial, it fails to signal redemption. Results from 2 laboratory studies, simulating different contexts and using research participants from 2 different countries, provide support for the prediction. The results offer important implications for those who might use reticence to respond to a perceived trust violation and also for those who must judge another's reticence.